2023
DOI: 10.2147/jbm.s394704
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Parameters and Their Correlation with Parasitemia Levels Among Malaria Infected Adult Patients at Jinella Health Center, Harar, Eastern Ethiopia: Comparative Cross-Sectional Study

Abstract: Background Malaria is a major public health problem with the highest morbidity and mortality in developing countries. Hematological changes play a great role in malaria pathogenesis through platelets and platelet parameters. However, the changes in platelet parameters are not clearly described in Ethiopia. Therefore, this study aimed to compare platelet parameters and their correlation with parasitemia among malaria-infected adult patients and healthy adults. Methods An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…In contrast to the previous study [6], our findings demonstrate no significant correlation between platelet count and parasite density. Furthermore, our results indicate a statistically significant elevation of TNF-α in the infected group compared to the non-infected group, consistent with previous research [16].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the previous study [6], our findings demonstrate no significant correlation between platelet count and parasite density. Furthermore, our results indicate a statistically significant elevation of TNF-α in the infected group compared to the non-infected group, consistent with previous research [16].…”
Section: Discussioncontrasting
confidence: 99%
“…The identification of secondary complications such as hematological abnormalities, involving disruptions to red blood cells, white blood cells, platelets, and elevated C-reactive protein (CRP) levels signifies the presence of inflammation in malaria cases [4], [5]. Thrombocytopenia, a common occurrence in malaria, stems from peripheral destruction, heightened platelet sequestration in the spleen, and consumption linked to disseminated intravascular coagulation [6]. Immune responses mediated by cytokines like TNFα and CRP are pivotal in the disease's progression, revealing insights into disease severity [7].…”
Section: Introductionmentioning
confidence: 99%
“…According to (Ratcliff et al, 2007), states that malaria infection causes abnormalities in the structure and function of platelets and there are several mechanisms postulated as the cause of thrombocytopenia including immune-mediated destruction, abnormalities in the platelet structure which are invaded by parasites and sequestration in the spleen (splenomegaly). This is in line with previous studies which also showed a correlation between the density of malaria parasites and the number of platelets (Asmerom et al, 2023;Margono et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…It is characterized by hemoglobin (Hb) levels that were below 12g/dl for women and 13g/dl for men (Al-Salahy et al, 2016). Studies have shown hematological abnormalities among malaria adult patients (Asmerom et al, 2023).…”
Section: Introductionmentioning
confidence: 99%